The effects of digital multi-tasking and task switching on working memory: A systematic review - Alsuwaylim, Amal Mubarak; Alshehri, Omar Abdullah; Alzahrani, Swead Yahya; Alsubaie, Faisal Bin Shabib Mosleet; Ali, Mohamed Osama; Yacoub, Shaban Atiya (Research Journal in Advanced Humanities, 2026)
Digital multitasking — defined as concurrent or rapidly alternating engagement with two or more technology-mediated tasks — has emerged as a pervasive feature of contemporary cognitive life with measurable consequences for working memory capacity and executive function. This systematic review synthesized empirical evidence from 28 studies published between 2016 and 2025, identified through searches of PubMed, PsycINFO, Web of Science, Scopus, and ERIC, following PRISMA 2020 guidelines. Findings converge on three domains: cognitive costs, academic performance, and neural mechanisms. Across behavioral, neuroimaging, and electrophysiological paradigms, digital multitasking consistently degraded working memory capacity, increased attentional lapses, elevated switch costs, and impaired metacognitive monitoring. In academic contexts, media multitasking during instruction reliably predicted reduced comprehension, recall, and cumulative achievement. At the neural level, chronic digital multitasking was associated with reduced functional efficiency within fronto-parietal control networks and diminished hippocampal encoding activity. Self-regulatory capacity emerged as a meaningful moderating variable. Methodological limitations — including cross-sectional designs, convenience sampling, and heterogeneous operationalizations — precluded meta-analytic synthesis and causal inference. Longitudinal research, standardized measurement, and rigorously evaluated interventions targeting digital self-regulation represent critical priorities for advancing this field.